(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article examines neuromarketing as an emerging interdisciplinary scientific field situated at the intersection of marketing, neuroscience, cognitive psychology, and behavioral economics. The study analyzes the epistemological foundations of neuromarketing, its methodological framework, and its transformation from an auxiliary analytical tool into an independent research paradigm. Particular attention is paid to the role of emotions, preconscious decision-making processes, and predictive cognitive mechanisms in consumer behavior. The paper discusses the methodological limitations of neural data interpretation and highlights the risks of neurodeterminism. Ethical challenges associated with the application of neuromarketing technologies are explored, emphasizing the need for neuroethical regulation and institutional accountability. The research argues that neuromarketing should be understood not as a reductionist biological model, but as a comprehensive framework integrating biological, cognitive, and social dimensions of human behavior. The future of the discipline is linked to its institutionalization, integration with artificial intelligence, and the development of responsible human-centered applications. Neuromarketing is ultimately presented as a key indicator of the transition toward an attention economy, where understanding human perception becomes a strategic resource.